2023
DOI: 10.21037/atm-22-2401
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial dynamics in neurological diseases: a narrative review

Abstract: Background and Objective: The mitochondrion is a crucial organelle for aerobic respiration and energy metabolism. It undergoes dynamic changes, including changes in its shape, function, and distribution through fission, fusion, and movement. Under normal conditions, mitochondrial dynamics are in homeostasis. However, once the balance is upset, the nervous system, which has high metabolic demands, will most likely be affected. Recent studies have shown that the imbalance of mitochondrial dynamics is involved in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 96 publications
0
1
0
Order By: Relevance
“…The outer mitochondrial membrane (OMM) mitofusins, MFN1 and MFN2, required for fusion of the OMM, while the inner mitochondrial membrane (IMM) protein optic atrophy-1, OPA1, is responsible for fusion of the IMM. Fission occurs in response to cell division and stress conditions and requires the translocation of the dynamin-related protein 1, DRP1, to the OMM, where it divides the mitochondria into two [ 9 , 75 ]. Two distinct fusion events have been described: complete fusion and partial fusion [ 76 ].…”
Section: Parkin Regulates Mitochondrial Dynamicsmentioning
confidence: 99%
“…The outer mitochondrial membrane (OMM) mitofusins, MFN1 and MFN2, required for fusion of the OMM, while the inner mitochondrial membrane (IMM) protein optic atrophy-1, OPA1, is responsible for fusion of the IMM. Fission occurs in response to cell division and stress conditions and requires the translocation of the dynamin-related protein 1, DRP1, to the OMM, where it divides the mitochondria into two [ 9 , 75 ]. Two distinct fusion events have been described: complete fusion and partial fusion [ 76 ].…”
Section: Parkin Regulates Mitochondrial Dynamicsmentioning
confidence: 99%
“…Similarly, in HD, abnormal DRP1 activation contributes to mitochondrial fragmentation and dysfunction, leading to neuronal degeneration [49]. Studies have shown that inhibiting the fission machinery through DRP1 or FIS1 knockdown results in the accumulation of oxidized mitochondrial proteins, reduced respiration, and impaired insulin secretion, which are associated with the progression of neurodegenerative diseases [60,[90][91][92][93].…”
Section: Protein Machinery In Mitochondrial Fissionmentioning
confidence: 99%